Association of oral microbiome with type 2 diabetes risk. (8th February 2017) - Long, J.; Cai, Q.; Steinwandel, M.; Hargreaves, M. K.; Bordenstein, S. R.; Blot, W. J.; Zheng, W.; Shu, X. O.
Abstract : Background and Objective: The oral microbiome may help to maintain systemic health, including how it affects blood glucose levels; however, direct evidence linking the oral microbiome with diabetes is lacking. Material and Methods: We compared the oral microbiome profiles of 98 participants with incident diabetes, 99 obese non‐diabetics and 97 normal weight non‐diabetics, via deep sequencing of the 16S rRNA gene. Results: We found that the phylum Actinobacteria was present significantly less abundant among patients with diabetes than among the controls ( p = 3.9 × 10 −3 ); the odds ratio (OR) and 95% confidence interval (CI) was 0.27 (0.11–0.66) for those individuals who had relative abundance higher than the median value. Within this phylum, five families and seven genera were observed, and most of them were less abundant among patients with diabetes. Notably, genera Actinomyces and Atopobium were associated with 66% and 72% decreased risk of diabetes with p ‐values of 8.9 × 10 −3 and 7.4 × 10 −3, respectively. Stratified analyses by race showed that most taxa in this phylum were associated with diabetes in both black and white participants. This phylum was also less abundant among non‐diabetic obese subjects compared to normal weight individuals, particularly genera Mobiluncus, Corynebacterium and Bifidobacterium, which showed p < 0.05. Conclusion: Our study revealed that multiple bacteria taxa in the phylum Actinobacteria are associated with the risk of type 2 diabetes. Some are also associated with the prevalence of obesity, suggesting that the oral microbiome may play an important role in diabetes etiology.